What's citizenship got to do with mental health? Rationale for inclusion of citizenship as part of a mental health strategy. Issue 3 (21st June 2019) - MacIntyre, Gillian; Cogan, Nicola Ann; Stewart, Ailsa Elizabeth; Quinn, Neil; Rowe, Michael; O'Connell, Maria
Abstract : Purpose: People with lived experience of mental health problems (MHPs) are often marginalised and have difficulty achieving community inclusion. Citizenship, a relatively novel concept in mental health, provides a means of understanding what is necessary for marginalised individuals and groups to gain a sense of belonging within their communities. By exploring the "what, why, how and who" of citizenship, the purpose of this paper is to provide a rationale for the inclusion of citizenship as part of a person-centred and holistic mental health strategy. Design/methodology/approach: A community-based participatory research (CBPR) approach, with peer researchers, was adopted to develop a model of citizenship within a Scottish context. The aim of the model is to link the concept of citizenship with specific strategies that systems, agencies and individuals can use within mental health policy and practice to promote greater inclusion and participation. Concept mapping was used as part of a mixed-methods participatory methodology and data were then analysed using multivariate statistical methods of multidimensional scaling and hierarchical cluster analysis. Findings: It is argued that using a CBPR approach, utilising concept mapping, encourages the development of a model of citizenship that is entirely grounded in the perspectives and lived experiences of people with MHPs. The need for adequate resources, preparatory work, training, research management and reflexive practice are key to the success of a CBPR approach with peer researchers. Originality/value: Working with peer researchers and key stakeholder groups is central to a CBPR approach and the implementation of a model of citizenship within mental health policy and practice. Developing a model of citizenship derived specifically from the experiences of people with lived experience is likely to promote their inclusion. It provides a means of challenging the structural deficits and inequalities that cause distress and prevent people with lived experience of MHPs of recovering their citizenship.